Pengelompokan Provinsi di Indonesia Menurut Indikator Pasar Tenaga Kerja - Ika Ayuningtyas; Muhammad Suryanata (Politeknik Statistika STIS, 2022)
Labour competitiveness is an essential issue in the global and national development agenda. The position of competitiveness of Indonesian workers is still below that of other countries. Labour competitiveness in Indonesia can be seen from key indicators of labour. This paper aims to group all provinces in Indonesia based on labor market indicators in 2019 using the Fuzzy C-Means (FCM) clustering method. All provinces managed to become 3 clusters. The first cluster consists of 2 provinces with fairly good competitive characteristics. The second cluster consists of 4 provinces having high labor productivity and average labor, as well as having challenges in other labor market indicators. The third cluster consists of 28 provinces with moderate indicator achievement characteristics. Accuracy indexes such as Dunn's Fuzziness Coefficients and Fuzzy Silhouette Index show a value close to 1. It indicates that the cluster has a strong structure. The right policies according to the target group are expected to encourage the improvement of the labour competitiveness so that they can contribute to achieving development goals.